SISTEM INFORMASI PELAYANAN JASA LAUNDRY BERBASIS WEB PADA TIRA LOUNDRY - Eka Permana; Depi Yuniar (Jurnal Teknologi Informasi dan Komunikasi, 2021)
Tira Laundry which is located on the street Walahar / Tegal Kelapa Subang is one where the laundry business provides kilogram washing services including washing and dry services, irons, washing clothes, washing pants, washing bed covers, and washing blankets. Based on existing problems, the Tira Laundry service data still uses manually from recording customer data to reports, data collection clothing that has not been taken by customers is still using ledgers, and consumer registration is still done by handwritten in a laundry activity book, so as to searching for customer data and other report data is experiencing difficulties and requires a long process. From this problem, a laundry service information system is created which contains customer data on the laundry tyra that occurs on a daily basis. In conducting this research using the methodology of collecting customer data and compiling conducting interviews about all activities related to customer service business data on tyra laundry having its address at Jalan Walahar / Tegal Kelapa Subang. The result to be achieved is to be able to create a web-based laundry service information system on tyra laundry, so as to increase the effectiveness of the efficiency of the tyra laundry business performance and facilitate the service of laundry data so that it can run quickly and easily.